Electrical drives and control techniques - Terörde, Gerd, ....- (Leuven : Acco, 2004)
The control, estimation and identification related to variable speed drives are fascinating research areas. It is practically impossible to cover the entire area within one textbook. The material presented concentrates on the basic features of the most common electrical drive systems, being still a fairly broad spectrum. It is intended to provide a modern approach to an understanding of the performance and control methods of electrical machines. This textbook is the result of many international lectures and courses on electrical drives and research projects completed in the research group ELECTA, a division of the department of Electrical Engineering of the Katholieke Universiteit Leuven in Belgium. It is directed to students following the course Electrical Drives and engineers working in the same field.
Keywords: Electriciteit ; aandrijftechniek; Elektromotorische aandrijving